2014
DOI: 10.7763/ijesd.2014.v5.498
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Quality of Reclaimed Wastewater Used for Irrigation of Public Parks in the United Arab Emirates

Abstract: Abstract-Bacteriological quality of reclaimed wastewater used for irrigation of thirty public parks located in Dubai and Sharjah was evaluated. Bacterial contaminants (Escherichia coli, Salmonella, Shigella and Enterobacter aerogenes) were tested by membrane filtration technique using Bismuth Sulphite Agar (BSA) and Violet Red Bile Agar (VRBA) media. The results showed the presence of Salmonella, Shigella, E. coli, Entereobacter aerogenes and other unidentified bacterial species on various selective media with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
(19 reference statements)
2
4
0
Order By: Relevance
“…Borehole water exhibited the lowest counts of Shigella spp., followed by the night-dam exit. The results are in agreement with findings by Al Mimi et al [30], who reported on 50 CFU/100 mL in a study where bacteriological quality of reclaimed wastewater used for irrigation was characterized in Dubai and Sharjah. In the present study, the low counts of Shigella spp.…”
Section: Bacterial Countssupporting
confidence: 93%
See 1 more Smart Citation
“…Borehole water exhibited the lowest counts of Shigella spp., followed by the night-dam exit. The results are in agreement with findings by Al Mimi et al [30], who reported on 50 CFU/100 mL in a study where bacteriological quality of reclaimed wastewater used for irrigation was characterized in Dubai and Sharjah. In the present study, the low counts of Shigella spp.…”
Section: Bacterial Countssupporting
confidence: 93%
“…However, in the night-dam exit, the counts were above 1000 CFU/100 mL, which showed an increase with movement and storage of treated wastewater post treatment. The findings were in a similar range to those observed by Al Amimi et al [30]. Standards for reclaimed water use in agriculture had been set from the minimum counts of 5 to 300 CFU/100 mL for various vegetables [31,32].…”
Section: Bacterial Countssupporting
confidence: 85%
“…16 Also, mean total bacterial colony count values in the range of 0.1–415 × 10 −5 and 1–107 CFU/100 mL have been isolated from wastewater used for irrigation at the golf courses in Spain, Portugal and the United Arab Emirates. 17,18 The differences in mean total bacterial colony count values may be due to the sources, types and levels of contamination of the wastewater used in irrigation in each country.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptosporidium oocysts have also been found in chlorinated water samples, as well as effluent samples collected from sewage treatment plants [114]-an indication that the water treatment systems (wastewater disinfection) have failed to eradicate the transmissible stages of Cryptosporidium in the water treatment process. In the UAE, it is not routine to test for the presence of Cryptosporidium oocysts in recreational water and reclaimed wastewater, while bacteriological (total and faecal coliforms) indices are the only biological parameters used to assess their water quality [114,130].…”
Section: Cryptosporidium Contaminating Water Resources In the Gcc Coumentioning
confidence: 99%